UPAYA KERJASAMA KEAMANAN INDONESIA-TIMOR LESTE STUDI KASUS PENYELUNDUPAN BAHAN BAKAR MINYAK DI KAWASAN PERBATASAN MOTAAIN TAHUN 2017-2019. - Nahak, Wendelina Yustina; Widhiyoga, Ganjar; Dipokusumo, Dipokusumo (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2021)
Mota’ain border is one of the cross-borders routes between Indonesia and Timor Leste which was inaugurated in 2016, after the independence of the state of Timor Leste in 2002. The border between one country and another is related to the sovereignty of each country which is influenced by international law. Indonesia-Timor Leste cooperates in various aspects to improve the stability and security of the two countries. This research focuses on the security cooperation efforts of Indonesia-Timor Leste case study of smuggling of fuel oil in the Mota’ain border area in 2017-2019. The main objective of this research is to find out how the security cooperation efforts carried out by the two countries against the smuggling of fuel oil. In additions the type of research and the date sources used are primary data and secondary data. Through this problem, the importance of the role of the government and security forces between the two countries in overcoming cases of the smuggling of BBM that often occur every year. BBM is the commodity energy need that gas strategic value in the world. Therefore, the author looks at the independent borderland approach where the population in this border area involves mutually beneficial economic activities. Residents cross illegally though the “Jalan Tikus” to launch fuel smuggling into Timor Leste. Apart from the fuel commodity, there are other basic necessities that are traditionality tratted by residents in the border area Indonesia and the country known as Timor Loro’sae, so that follow-up is necessary from government and non-government agencies of interest such as security forces, immigration, customs and national agency for border management from the two countries to deal with the illegal fuel smuggling case. Keywords: Border Diplomacy, BBM Smuggling, Bilateral Relation Indonesia-Timor Leste.